ASSESSMENT OF BIOACTIVE METABOLITES FROM THE ROOT ENDOPHYTE ISOLATED FROM CASUARINA JUNGHUHNIANA Miq. - Bose, Priyom; Gowrie, Uma (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Casuarina junghuhniana Miq is a well known multipurpose tree belonging to family Casuarinaceae. This tree has the ability to sustain in different edaphic and extreme environmental conditions. The root extract of this tree is a rich source of potential secondary metabolites. Therefore, the main objective of this study is to isolate fungal root endophyte from this tree and to determine its bioactive compound which can be utilized in agriculture and pharmaceutical industries. Methods: Casuarina junghuhniana Miq root samples were collected from the State Forestry Research Institute, Neyveli, Tamil Nadu. Isolation of fungal endophyte was carried out using Potato Dextrose Agar medium. The qualitative and quantitative phytochemicals screening and enzyme assays were carried out using standard procedures. Antimicrobial assay was tested against different pathogens using well diffusion method. Further, the phytochemicals in the root extract was evaluated using FTIR, HPLC and GC MS studies. Result: Among the isolated endophytes, the dominant isolate (CJN5) was identified as Aspergillus sp which showed positive result in the production of industrially important enzymes, namely, cellulase, lipase and amylase The qualitative screening revealed the presence of various phytoconstituents Total phenolic content of CFE (208.20±2 mg/g) was found higher than CME(165.5±3mg/g). The total flavonoid content of CFE (25.95±2 mg/g) was also found higher than CME (3.59±2 mg/g) using respective standards. Antimicrobial activity showed maximum zone of inhibition against Pseudomonas aeruginosa (bacterial pathogen) (24±0.1cm) and Fusarium oxysporum (fungal phytopathogen) (34 ± 0.2cm).FTIR analysis showed the presence of varied functional groups. HPLC study revealed the presence of Gallic acid acid and Salicylic acid. Several peaks were obtained in GCMS analysis which indicates the presence of different secondary metabolites. Conclusion: Aspergillus sp, isolated from the root of Casuarina junghuhniana Miq is a promising source of bioactive compounds which can be utilised in agriculture and pharmaceutical industries. Key words: endophyte, Casuarina junghuhniana, phytochemical, antimicrobial, HPLC, GC MS